The Effect of Traditional Play Activities on Gross Motor Skills of Children - A. Ulmi Juniarti; Azizah Amal; Muhammad Akil Musi; Fitriani Dzulfadhilah (CV. Creative Tugu Pena, 2025)
This study aimed to determine the gross motor skills of children aged 5–6 years before and after engaging in traditional play activities at TK Kemala Bhayangkari 20, Pangkep Branch. A quantitative approach with a quasi-experimental design was employed. The population of this study consisted of all students at TK Kemala Bhayangkari 20, Pangkep Branch, totaling 61 children. Purposive sampling was used to select 20 children, who were divided into two groups: 10 children in the experimental group and 10 children in the control group. Data were collected through observation and performance tests, while data analysis was conducted using descriptive statistics and non-parametric tests. The results showed that the implementation of traditional games significantly contributed to the improvement of children’s gross motor skills, particularly in aspects of balance, agility, and coordination. The findings indicated that: (1) children in the experimental group were initially categorized as “Not Yet Able” before the intervention and improved to the “Very Able” category after the intervention; (2) children in the control group were initially categorized as “Not Yet Able,” and after participating in seesaw play activities, they showed only a slight improvement, placing them in the “Fairly Able” category; and (3) statistical analysis revealed a significant effect of traditional game interventions on the development of gross motor skills among children aged 5–6 years in the experimental group. Therefore, it was concluded that traditional games had a positive effect on the gross motor development of kindergarten children.